THE IMPLICATIONS OF CIRCULAR ECONOMY DEVELOPMENT AT EUROPEAN LEVEL - Laurențiu Paul Barangă; Elena-Ioana Țanea (Revista de Studii Financiare, 2023)
In the context of the production of more than 2,5 billion tons of waste every year in the European Union, the circular economy is a matter of significant importance, debated in the European area and beyond. The transition to the circular economy involves reducing waste to the lowest level and replacing the traditional linear purchase-use-disposal economy. Thus, given the World Bank’s 2050 estimates (2018), which support an increase in annual waste production by 70% and the premise that the United Nations’ Sustainable Development goals made, that the population will require the resources of three planets, moving toward a circular economy is a necessity for both the environment and society.